Genetic risk factors associated with gallbladder carcinoma - Khan, Saara Mudassir; Muhammad, Jibran Sualeh; Khan, Asra; Khan, Muhammad Rizwan; Kulsoom Ghias, Kulsoom (Pakistan Journal of Physiology, 2019)
Gallbladder cancer (GBC) is an aggressive biliary tract cancer with wide geographic diversity. Various genetic modifications of GBC, including mutations in p53, KRAS, p16 and retinoblastoma (RB) gene. Mutations in p53 lead to carcinoma, while point mutations in KRAS leads to hyperplasia. KRAS mutations are often found in both pancreatico-biliary ducts junction and in neoplastic loci in gallbladder polyps. The 5-year survival rate for overall GBC patients is <1%. GBC is crucial for diagnostic and prognostic markers and potential drug targets. Ovid-MEDLINE, PubMed, CINHAL and Google Scholar databases were searched using keywords gallbladder carcinoma, neoplasia, tumour, tumor, adenocarcinoma, biliary tract carcinoma, gene mutations, KRAS, p53, RB, and p16. Ten out of 470 research articles were finally included. It was observed that loss of heterogeneity and mutations of KRAS, p53, p16 and RB involve in the disruption of cell cycle leading to continuous cell division and cancer. Pak J Physiol 2019;15(4):66?70